Socialization of the Interest in Saving Movement for Early Childhood at Al-Hibbah Lampisang Kindergarten, Aceh Besar - Susi Wardani; Puji Aryani; Ajiran Ramadhan; M Alfian Aldi; Cut Sulfa Rahmadian; Huswatul Khaira (Bulletin of Social Studies and Community Development, 2023)
Abstract: This Community Servce was carried out by Sharia Banking Lecturer and Students, Faculty of Islamic Religion, Muhammadiyah University of Aceh to provide Socialization of the Interest in Savings Movement in Early Childhood at Al-Hibbah Kindergarten Lampisang Aceh Besar with the aim of providing an understanding of saving in early childhood and also being able to provide a very good benefit for the future and can motivate children about the importance of saving so that it raises awareness in children to set aside some of their pocket money to save. The result of this Community Service activity is that is hoped that young children will understand better  how important it is to save from an early age.    Keywords: socialization, interest, saving, early